Evaluation of Peripheral Blood Leukocytes as a Surrogate for RNA-Seq Detection of Gene Expression in Stress Axis Tissues of Mature Brahman Cows. (7th May 2021) - Earnhardt, Audrey L; Baker, Emilie C; Cilkiz, Kubra Z; Riley, David G; Ghaffari, Noushin; Littlejohn, Brittni P; Collins, Haley C; Riggs, Penny K; Long, Charles R; Cardoso, Rodolfo C; Randel, Ron D; Welsh, Thomas H
Abstract: Longitudinal studies of gene expression where sampling certain organ systems is precluded may become more feasible if a more accessible, representative biological sample could be identified. The objective of this study was to determine whether peripheral blood leukocytes (PBL) could be an effective surrogate for assessing gene expression differences within neuroendocrine tissues that regulate stress responses. Specifically, leukocyte samples and stress axis tissues, including the paraventricular region of the hypothalamus, anterior pituitary gland, adrenal cortex, and adrenal medulla were isolated from humanely slaughtered 5-yr-old Brahman cows (n = 8). RNA was extracted from each sample and gene expressions were calculated using bioinformatic approaches of RNA-Seq analysis. Differentially expressed genes (DEG) between adrenal axis tissue RNA and PBL RNA were identified using the edgeR Package from Bioconductor, R. More than 3, 000 DEGs were identified in each tissue relative to the PBLs. Overall, higher gene expression levels were observed in the hypothalamus vs PBL, while the remaining tissues had reduced expression compared to PBL (Table 1). Pearson correlation values were calculated from the mean normalized gene count in the PBL and tissues for genes (n = 17) important for stress response and metabolism to assess PBL as a possible surrogate for gene expression analyses (Table 2). Only two genes, oxytocin and 11β-hydroxylase, were positively correlated (P < 0.05) between PBL and specific tissue gene expression. As typically observed among different cell types, gene expression differences exist between the PBL and various tissues of the HPA axis. Therefore, it remains to be determined if gene expression in the surrogate PBL will shift in a direction similar to that of specific adrenal axis tissue of mature Brahman cows exposed to stressors during key developmental periods.